2012
DOI: 10.1371/journal.ppat.1002471
|View full text |Cite
|
Sign up to set email alerts
|

(Homo)glutathione Deficiency Impairs Root-knot Nematode Development in Medicago truncatula

Abstract: Root-knot nematodes (RKN) are obligatory plant parasitic worms that establish and maintain an intimate relationship with their host plants. During a compatible interaction, RKN induce the redifferentiation of root cells into multinucleate and hypertrophied giant cells essential for nematode growth and reproduction. These metabolically active feeding cells constitute the exclusive source of nutrients for the nematode. Detailed analysis of glutathione (GSH) and homoglutathione (hGSH) metabolism demonstrated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 69 publications
2
46
0
Order By: Relevance
“…3 can occur, at least transiently, in other conditions that involve oxidative stress (Vanacker et al, 2000;Bick et al, 2001;Gomez et al, 2004a). Such changes in glutathione seem to be of functional importance in linking intracellular H 2 O 2 to pathogenesis-related (PR) responses (Han et al, 2013a,b), and several other studies point to an important role of glutathione in determining plant responses to biotic stress (Ball et al, 2004;Parisy et al, 2007;Schlaeppi et al, 2008;Baldacci-Cresp et al, 2012). The mechanisms by which glutathione is involved in oxidative stress signalling remain to be elucidated but may involve processes such as formation of protein disulfides, S-glutathionylation, or S-nitrosylation (Dixon et al, 2005;Feechan et al, 2005;Tada et al, 2008;Palmieri et al, 2010;Zaffagnini et al, 2012).…”
Section: Ascorbate and Glutathionementioning
confidence: 99%
“…3 can occur, at least transiently, in other conditions that involve oxidative stress (Vanacker et al, 2000;Bick et al, 2001;Gomez et al, 2004a). Such changes in glutathione seem to be of functional importance in linking intracellular H 2 O 2 to pathogenesis-related (PR) responses (Han et al, 2013a,b), and several other studies point to an important role of glutathione in determining plant responses to biotic stress (Ball et al, 2004;Parisy et al, 2007;Schlaeppi et al, 2008;Baldacci-Cresp et al, 2012). The mechanisms by which glutathione is involved in oxidative stress signalling remain to be elucidated but may involve processes such as formation of protein disulfides, S-glutathionylation, or S-nitrosylation (Dixon et al, 2005;Feechan et al, 2005;Tada et al, 2008;Palmieri et al, 2010;Zaffagnini et al, 2012).…”
Section: Ascorbate and Glutathionementioning
confidence: 99%
“…Indeed, previous experiments in B. rapa showed that inhibition of auxin transport results in decreased clubroot symptoms . GSH accumulation has been demonstrated to be positively related to the infection processes in plant nematode interactions and in nitrogen-fixing symbiosis (Baldacci-Cresp et al 2012;Frendo et al 2005). To refine the understanding of the GSH metabolism during clubroot development, it would now be important to clarify the actual redox status of this molecule in root tissues.…”
Section: Do Higher Gsh Contents Play a Favorable Role In Plant Or Patmentioning
confidence: 99%
“…Although the origins and structure of GCs and syncytia are different, both feeding sites function as transfer cells surrounded by de novo induced vascular vessels to nourish the nematode (Hoth et al , , Bartlem et al ). Other common features between gall formation and grafting are starch accumulation (Baldacci‐Cresp et al , Melnyk et al ) and the tight regulation of the auxin/cytokinin balance (Cabrera et al , Melnyk et al ). In line with this, gall and syncytium formation have been described as a process conceptually related to grafting and proposed as models to study vascular reconnection (Melnyk ).…”
Section: Discussionmentioning
confidence: 99%